Uncertainty, fragility, resilience - Ernesto Antonini (Agathón)
The consequences of climate change and the recurrent shortage of vital resources produce an extreme and growing fragility of all systems, both biological and technical, subjected to continuous and increasingly less predictable disturbances. In this perspective, the strategy that pretends to maintain static equilibrium at any cost is ineffective. Therefore, we look with attention at the adaptive approach, based on reactivity, ability to self-repair individual parts and fault tolerance, which has always enabled living organisms to survive in hostile contexts. This attitude of biological systems to adopt dynamic responses to the perturbative actions of their balance proves to be extraordinarily effective and intrinsically efficient, to the point of proposing itself as a paradigm to be inspired to organize even artificial systems.